EVIDENCE IN THE ARBITRATION PROCESS. STUDYING THE EXPERIENCE OF SWEDEN AND THE ARBITRATION INSTITUTE OF THE STOCKHOLM CHAMBER OF COMMERCE (World Bulletin of Management and Law, 2024)
This article provides the deep analysis on theoretical and legal aspect of evidences in international investment arbitration process. The main focus of this paper is to examine the burden of proof, the process of submission of evidences in investment arbitration process and study the experience of that process in Sweden and the Arbitration Institute of the Stockholm Chamber of Commerce
Keywords: Investment; Arbitration; Evidence; Alternative